2005
DOI: 10.1055/s-2005-864161
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a New Saponin and Cytotoxic Effect of Saponins from the Root ofPlatycodon grandiflorumon Human Tumor Cell Lines

Abstract: A novel triterpenoid saponin, deapioplatycoside E (1) was isolated from the root extract of Platycodon grandiflorum, together with the seven known saponins 2 - 8, i. e., platycoside E (2), deapioplatycodin D3 (3), platycodin D3 (4), polygalacin D2 (5), platycodin D2 (6), deapioplatycodin D (7) and platycodin D (8). The structure of the new saponin 1 was determined on the basis of spectral analysis and chemical evidence. The crude saponin fraction (ED50: ca. 10 - 15 microg/mL) and compounds 6 - 8 (ED50: ca. 4 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 8 publications
2
65
0
Order By: Relevance
“…1 Although many compounds have been isolated from P. grandiflorum roots, PD has shown the most potent biological activities of all the platycodin saponins. [2][3][4][5][6][7] Recent studies have shown that PD effectively induces apoptosis in many cancer cells; 8,9 however, the underlying cellular and molecular mechanisms responsible for PD's anticancer activity in human leukemia cells are not known. In our study, we first provided the apoptotic mechanisms induced by PD in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although many compounds have been isolated from P. grandiflorum roots, PD has shown the most potent biological activities of all the platycodin saponins. [2][3][4][5][6][7] Recent studies have shown that PD effectively induces apoptosis in many cancer cells; 8,9 however, the underlying cellular and molecular mechanisms responsible for PD's anticancer activity in human leukemia cells are not known. In our study, we first provided the apoptotic mechanisms induced by PD in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…PD contains a crucial bioactive component responsible for diverse effects such as anti-inflammatory, antiallergic and cholesterol-lowering activities. [3][4][5][6][7] Although recent studies have also shown that PD can induce apoptosis in several cancer cells, 8,9 until now no clear or unique mechanisms of PD-induced apoptosis are known.…”
mentioning
confidence: 99%
“…Its roots are popular in traditional Chinese medicine because they are abundant in triterpenoid saponins (Ishii et al, 1978;Fu et al, 2006) and used as a remedy for cough, cold, bronchitis, asthma, and sore throat (Germida et al, 1998;Lee et al, 2004). The root of balloon flower is commonly called doraji in South Korea, jie geng in China, and kikyo in Japan, and total saponin content varies among the germplasm resources (Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These facts have triggered an extended search for new drugs to treat infectious diseases (Fostel & Lartey, 2000). Cancer treatment is poorly defined in terms of traditional folk medicine; nevertheless, some medicinal plants used for the treatment of infectious diseases, fever, and inflammation have shown cytotoxic in vitro activity against human tumor cell lines and are an important source of potential anticancer agents (Cragg & Newman, 2005;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%